Effects of Mucin and DNA Concentrations in Airway Mucus on Pseudomonas aeruginosa Biofilm Recalcitrance - Kaitlyn R. Rouillard; William J. Kissner; Matthew R. Markovetz; David B. Hill (mSphere, 2022)
ABSTRACT The pathological properties of airway mucus in cystic fibrosis (CF) are dictated by mucus concentration and composition, with mucins and DNA being responsible for mucus viscoelastic properties. As CF pulmonary disease progresses, the concentrations of mucins and DNA increase and are associated with increased mucus viscoelasticity and decreased transport. Similarly, the biophysical properties of bacterial biofilms are heavily influenced by the composition of their extracellular polymeric substances (EPS). While the roles of polymer concentration and composition in mucus and biofilm mechanical properties have been evaluated independently, the relationship between mucus concentration and composition and the biophysical properties of biofilms grown therein remains unknown. Pseudomonas aeruginosa biofilms were grown in airway mucus as a function of overall concentration and DNA concentration to mimic healthy, and CF pathophysiology and biophysical properties were evaluated with macro- and microrheology. Biofilms were also characterized after exposure to DNase or DTT to examine the effects of DNA and mucin degradation, respectively. Identifying critical targets in biofilms for disrupting mechanical stability in highly concentrated mucus may lead to the development of efficacious biofilm therapies and ultimately improve CF patient outcomes. Overall mucus concentration was the predominant contributor to biofilm viscoelasticity and both DNA degradation and mucin reduction resulted in compromised biofilm mechanical strength. IMPORTANCE Pathological mucus in cystic fibrosis (CF) is highly concentrated and insufficiently cleared from the airway, causing chronic inflammation and infection. Pseudomonas aeruginosa establishes chronic infection in the form of biofilms within mucus, and this study determined that biofilms formed in more concentrated mucus were more robust and less susceptible to mechanical and chemical challenges compared to biofilms grown in lower concentrated mucus. Neither DNA degradation nor disulfide bond reduction was sufficient to fully degrade biofilms. Mucus rehydration should remain a priority for treating CF pulmonary disease with concomitant multimechanistic biofilm degradation agents and antibiotics to clear chronic infection.